SUBSTITUTION MILLE FEUILLE WITH SORGUM FLOUR BASED SNACK INOVATION ON LOCAL FOOD - Wika Rinawati, Sumaryana (Prosiding Pendidikan Teknik Boga Busana, 2020)
This study aims to determine the recipe mille feuille with substitution of sorghum were accepted by the public and know the nutritional information on product substitution mille feuille with sorghum flour. Making the mille feuille using a percentage of 0%, 10%, 15%, 20%. Testing is done by trial and selected that have the characteristics of a good development in terms of taste, color, aroma and texture. In making of mille feuille, substitution of sorghum flour to wheat flour selected with a percentage of 20% for sensory still acceptable. A level test of the product mille feuille done using hedonic test with a range of 1-4 scale (1 = dislike, 4 = strongly like). Analysis of nutritional value information contained in the product mille feuille using proximate analysis. Proximate analysis to determine levels of carbohydrates, fat, protein, ash and water. The study of public acceptance shows the measurement results of color parameters of 3.5, the aroma of 3.7, 3.4 texture, flavor 3.5, overall show highly preferred product. Keywords: mille feuille, substitution, sorghum flour